2019
DOI: 10.1007/s00402-019-03241-4
|View full text |Cite
|
Sign up to set email alerts
|

Low acceptance of osteoanabolic therapy with parathyroid hormone in patients with fragility fracture of the pelvis in routine clinical practice: a retrospective observational cohort study

Abstract: Introduction A recent randomized controlled trial has reported full patient compliance and no adverse events from therapy with parathyroid hormone (PTH) for osteoporosis and accelerated healing of fragility fractures of the pelvis. The purpose of the presented study was to evaluate if similar results can be achieved with comprehensive PTH therapy in routine clinical practice. We hypothesised that patients' burden of PTH therapy is underestimated in the literature. Patients and methods Osteoanabolic PTH therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Maier et al found that only 50% of their 93 patients received anti-osteoporotic therapy [ 19 ]. Suhm et al stated that only 46% of their 50 follow-up patients received any form of anti-resorptive therapy and additional fractures occurred in 22% [ 31 ]. Although the occurrence of isolated pubic rami fractures is a serious adverse event for elderly persons, prevention of further fractures with anti-resorptive drugs seems not to be widely accepted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maier et al found that only 50% of their 93 patients received anti-osteoporotic therapy [ 19 ]. Suhm et al stated that only 46% of their 50 follow-up patients received any form of anti-resorptive therapy and additional fractures occurred in 22% [ 31 ]. Although the occurrence of isolated pubic rami fractures is a serious adverse event for elderly persons, prevention of further fractures with anti-resorptive drugs seems not to be widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence of isolated pubic rami fractures is a serious adverse event for elderly persons, prevention of further fractures with anti-resorptive drugs seems not to be widely accepted. One important part of geriatric co-management is exploration of bone metabolism and treatment of osteoporosis for the prevention of the occurrence of additional fragility fractures [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Intermittent TPTD administration also has been reported to accelerate pelvic fracture and distal radial fracture healing by enhancing callus formation. [24][25][26] Sixty-five patients who had been treated with pelvic fractures divided into 21 patients received a once-daily injection of 100 mg of PTH 1-84, and 44 patients served as the control group. At week 8, all fractures in the treatment group and 4 fractures in the control group had healed (healing rate, 100% vs. 9.1%) and mean pain and function score (time up and go test, 22.9 vs. 54.3 sec; P<0.001), even nonunion was not detected at the latest visit.…”
Section: Does Tptd Decrease the Fracture Healing Time?mentioning
confidence: 99%
“…Intermittent TPTD administration also has been reported to accelerate pelvic fracture and distal radial fracture healing by enhancing callus formation [ 24 - 26 ]. Sixty-five patients who had been treated with pelvic fractures divided into 21 patients received a once-daily injection of 100 mg of PTH 1-84, and 44 patients served as the control group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The indications for drug therapy include a history of fragility fractures, T value <−2.5 or T value > − 1 but <−2.5, and other risk factors. Previous studies have shown that drug therapy is effective in the treatment of osteoporosis and in the reduction of fracture risk 95,96 …”
Section: Clinical Questionsmentioning
confidence: 99%